Zirkonium und seine Verbindungen (außer Zirkoniumdioxid) [MAK value documentation in German language, 2019]. Issue 3 (1st August 2019) - Hartwig, A.; ,
Abstract: The German Commission for the Investigation of Health Hazards of Chemical Compounds in the Work Area has re‐evaluated the maximum concentration at the workplace (MAK value) for zirconium and its compounds. No new data are available that would be relevant for the derivation of a MAK value for zirconium compounds, with the exception of zirconium dioxide (see documentation "Zirconium dioxide", to be published in 2019). Therefore, zirconium and its compounds (except zirconium dioxide) are listed in Section II b of the List of MAK and BAT Values. Based on the new human and animal data, zirconium and its compounds (except zirconium dioxide) are not regarded as sensitizers. Dermal absorption does not contribute to systemic toxicity.